Leveraging Enterprise Architecture for Digital Transformation Adaptation Challenges in Higher Education Institutions - et.al, Wan Faezah Abbas (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The rapid proliferation and emergence of mobile, digital technologies, smartphone devices, big data, cloud computing and Internet of Things (IoT) have given rise to a new era of Digital Transformation (DT). DT is shifting not only technological advancements but also involves changes to business processes, organization structure, business models, managerial and culture. Higher Education Institution (HEI) are undergoing some forms of DT and is affected by these changes. Technology is changing the way many HEIs operate and to ensure survival, HEI needs to adapt to DT changes. However, HEIs are facing difficulties in adapting to DT. The main objective of this paper is to identify DT adaptation challenges in HEI based on literature review. Result from the literature review lists the HEI DT adaptation challenges and Enterprise Architecture(EA) is identified as a facilitator and enabler to support DT initiatives.